Consistency of Reporting for Stressful Life Events Among Nondeployed Soldiers. Issue 10 (8th April 2016) - Pless Kaiser, Anica; Proctor, Susan P.; Vasterling, Jennifer J.
Abstract : Objectives: Measurement of stress exposure is central to understanding military mental health outcomes. Although temporal stability of combat event reporting has been examined, less is known about the stability of reporting for noncombat events in military samples. Objectives are to examine consistency in reporting stressful life events in nondeployed U.S. Army soldiers and its association with posttraumatic stress disorder (PTSD) symptomatology. Method: Examined reporting consistency over approximately 8 months among 466 soldiers. Regression models examined factors associated with decreased, increased, and stable reporting. Results: Stability of the number of events endorsed over time was high. However, item‐level agreement was slight to moderate (kappas: .13–.54), with inconsistencies due primarily to decreased reporting. After adjusting for covariates and initial PTSD, second assessment PTSD was associated with increased and stable reporting. Conclusions: Inconsistent reporting extends beyond combat events to other stressful life events in military personnel and is associated with PTSD.